GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI - Innes Maeya Sofa; Wiwik Widayati; Supratiwi . (Journal of Politic and Government Studies, 2014)
Economic empowerment that involves the participation of society at large , makes a lot of SME ( Small Medium Enterprises ) that grow and evolve , becoming even safety valve for the nation's economic recovery . This is a popular economic sector entities as economic actors who have proven not only to survive , even say